Oxidative Damage Is Influenced by Diet But Unaffected by Selection for Early Age of Oviposition in the Marula Fly, Ceratitis cosyra (Diptera: Tephritidae) - Malod, Kevin; du Rand, Esther E.; Archer, C. Ruth; Nicolson, Susan W.; Weldon, Christopher W. (Frontiers in Physiology, 2022)
The expression of life-history traits, such as lifespan or reproductive effort, is tightly correlated with the amount and blend of macronutrients that individuals consume. In a range of herbivorous insects, consuming high protein to carbohydrate ratios (P:C) decreases lifespan but increases female fecundity. In other words, females face a resource-based trade-off between lifespan and fecundity. Redox metabolism may help mediate this trade-off, if oxidative damage is elevated by reproductive investment and if this damage, in turn, reduces lifespan. Here, we test how diets varying in P:C ratio affect oxidative damage and antioxidant protection in female and male of the marula fly, Ceratitis cosyra (Diptera: Tephritidae). We use replicated lines that have been subjected to experimental evolution, and differ in their lifespan and reproductive scheduling. We predicted that high fecundity would be associated with high oxidative damage and reduced antioxidant defences, while longer lived flies would show reduced damage and elevated antioxidant defences. However, higher levels of oxidative damage were observed in long-lived control lines than selection lines, but only when fed the diet promoting lifespan. Flies fed diets promoting female fecundity (1:4 and 1:2 P:C) suffered greater oxidative damage to lipids than flies fed the best diet (0:1 P:C) for lifespan. Total antioxidant capacity was not affected by the selection regime or nutrition. Our results reiterate the importance of nutrition in affecting life-history traits, but suggest that in C. cosyra, reactive oxygen species play a minimal role in mediating dietary trade-offs between lifespan and reproduction.